Potential long-term health effects of a SARS-CoV-2 infection - Altmann, Danny (Henry Stewart Talks, 2020)
Potential long-term health effects of a SARS-CoV-2 infection, Parallels with other virus infections, Hypotheses on why long-term health effects are occurring, Required next steps